Familial lethal cardiomyopathy with mental retardation and scapuloperoneal muscular dystrophy. Issue 12 (December 1986) - Bergia, B; Sybers, H D; Butler, I J
Abstract : A family is described with a neuromuscular disorder characterised by possible X-linked recessive inheritance, a benign, slowly progressive muscular dystrophy with predominant humeroperoneal distribution and lack of contractures or pseudohypertrophy, central nervous system involvement, myopia and lethal cardiomyopathy. The possibility of cardiac transplant as life-saving therapy is suggested.